IoT Application in a Vision-Based Security System at the At-Taqwa Mosque in Cijulang - Hiron, Nurul; Nurdiansyah, Rian; M.Aris Risnandar; Andri Ulus R; Helmy Dzulfikar; Aldy Putra Aldya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The use of Internet of Things (IoT) technology has become a trend in various areas of life. In the context of security and monitoring, IoT applications can provide innovative solutions to improve monitoring and protection. This community service program aims to apply the IoT concept in a vision-based security system at the At-Taqwa Cijulang Mosque. Through the integration of sensors and vision devices connected to an IoT network, this program proposes a more effective and efficient solution for monitoring mosque security. Motion and presence sensors will be installed to detect suspicious activity and manage the environment within the mosque. The vision-based security system will use cameras connected to an IoT network to monitor and identify people and activities occurring in the mosque area. In addition, a mobile application will be developed to provide real-time monitoring access to mosque administrators and the local community. The results of the service showed increased security in the environment around the mosque as well as increased awareness of security in the community around the At-Taqwa Cijulang Mosque.